3D gel printing of alumina ceramics followed by efficient multi-step liquid desiccant drying. Issue 13 (October 2021) - Xie, Hehan; Yang, Xianfeng; Liu, Peng; Xu, Xiewen; Zhou, Zhe; Zhao, Wei; Shen, Zhijian
Abstract: Dense alumina ceramics were additively manufactured efficiently through a 3D gel printing process. Hydroxyethyl cellulose (HEC) was applied to ensure the printability and rigid of the gel made from boehmite. A multi-step liquid desiccant drying method was implemented to improve the drying efficiency. The results showed that the solid loading and HEC addition were two useful parameters for adjusting the rheology properties of the gel to make it suitable for 3D printing. With polyethylene glycol(PEG) added as liquid desiccants, the printed bodies with section size of 10 mm could be dried within 26 h during which the deformation and crack formation was avoided despite a high linear shrinkage of 45 % was encountered. The successful preparation of dense monolithic alumna ceramics parts with an average grain size of 1 μm, 99 % of the theoretical density and a flexural strength of 380 ± 45 MPa indicated the potential of this process.